Wednesday
March 29, 2017

Post a New Question

Posted by on .

x^2 - 14 x + 13 = 30 y
x^2 - 14 x = 30 y - 13
x^2 - 14 x + 49 = 30 y + 36 ****
(x-7)^2 = 30 y + 36
x - 7 = +/- sqrt (30 y + 36)
x = 7 +/- sqrt (30 y + 36)

where did you get the 49 or 36

  • Math - ,

    I did it below after you asked

  • Math - ,

    which one is the the bottem or the top
    number in exponents

  • Math - ,

    Here again:
    ========
    #

    Completing the square
    x^2 + a x = something
    x^2 + a x + (a/2)^2 = something + (a/2)^2
    so
    if
    x^2 -14 x = something
    then
    x^2 - 14 x +(14/2)^2 = something + (14/2)^2
    or
    x^2 - 14 x + 49 = something + 49
    (x-7)^2 = something + 49
    x - 7 = +/- sqrt (something + 49)

    by taking half the second coefficient and squaring it, I get a perfect square.

    # Math - Damon, Wednesday, April 23, 2008 at 10:13pm

    and 49 - 13 = 36

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question